Domestic Worker, Transnational Advocacy and the State of Exception: A Case Study on The Advocacy of Domestic Worker’s Rights in Indonesia - Bastari, Gema Ramadhan (Political Science Program, Universitas Negeri Semarang, 2018)
This paper explains why domestic workers (PRT) remain not considered as formal workers in Indonesia. This problem becomes very urgent as PRT covers 76% of the national labor population and there has been considerable pressure from transnational community. This question is answered by applying Agamben's theory of state of exception. This paper deploysdiscourse analysis method to examine a number of texts related to the Government of Indonesian's stance and the advocacy for PRT’s rights in Indonesia. This study finds that the Government of Indonesia has established a state of exception allowing to ignore PRT’s rights as workers under existing law. The study, then, concludes that the Government of Indonesian cannot be expected to meet PRT’s rights. Consequently, the strategy of advocacy should be directed to encourage other countries to push Indonesia so as to meet PRT’s rights.